When you are born matters: An age-period-cohort analysis of multimodality. (January 2021) - An, Zihao; Heinen, Eva; Watling, David
Highlights: We examined the net effects of age, period, and cohort effects on multimodality. Individuals tend to be less multimodal as they get older. Cohort effects, compared to period effects, explain the changes in multimodality better. Multimodality is the lowest for the baby boomer cohort. Policies required to tackle the falling trend in multimodality for the post-1985 cohort. Abstract: Multimodality – the behavioural phenomenon of using multiple modes of transport – has been suggested to be a useful indicator of an individual's willingness to adopt more sustainable transport alternatives. Analysing temporal patterns in multimodality provides the opportunity to understand the formation of multimodal practices. Yet the existing studies on this topic share one limitation: they fail to simultaneously incorporate into their analysis the three interconnected temporal dimensions: age, period, and (birth) cohort. Given that age, period, and cohort are mathematically intertwined, the omission of any of these three variables may lead to biased explanations. Using the National Travel Survey in England, from 2001 to 2017, this research explored the extent to which individual multimodality varied by age, period, and cohort. We adopted the hierarchical age-period-cohort model to estimate the net effects of age, period, and cohort on multimodality. Our analyses showed that travellers tend to be less multimodal as they get older. The age effects may be moderated by work or physical mobility constraints, which accelerate the decrease in multimodality before or after reaching 30 years old, respectively. Individual multimodality exhibited significant variation across periods and cohorts. The total variance in multimodality accounted for by cohorts was larger than that explained by periods. Multimodality reached the lowest level for cohorts born between 1945 and 1969. This may be partially explained by the joint influence of multiple spatial mobility constraints as well as by the distinctive early life conditions and formative experience of baby boomers in terms of driving during the post-war economic expansion.